FOXO1 inhibits prostate cancer cell proliferation via suppressing E2F1 activated NPRL2 expression. (15th September 2021) - Tang, Yu; Jiang, Li; Zhao, Xin; Hu, Daixing; Zhao, Guozhi; Luo, Shengjun; Du, Xiaoyi; Tang, Wei
Abstract: Previous studies in our lab suggest that nitrogen permease regulator 2‐like (NPRL2) upregulation in prostate cancer is associated with malignant behavior and poor prognosis. However, the underlying mechanisms of NPRL2 dysregulation remain poorly understood. This study aimed to explore the transcription factors (TFs) contributing to NPRL2 dysregulation in prostate cancer. Potential TFs were identified using prostate tissue/cell‐specific chromatin immunoprecipitation (ChIP)‐seq data collected in the Cistrome Data Browser and Signaling Pathways Project. Dual‐luciferase assay and ChIP‐qPCR assay were conducted to assess the binding and activating effect of TFs on the gene promoter. Cell Counting Kit‐8 and colony formation assays were performed to assess cell proliferation. Results showed that E2F1 is a TF that bound to the NPRL2 promoter and activated its transcription. NPRL2 inhibition significantly alleviated E2F1 enhanced cell proliferation. Kaplan–Meier survival analysis indicated that E2F1 upregulation was associated with unfavorable progression‐free survival and disease‐specific survival. FOXO1 interacted and E2F1 in both PC3 and LNCaP cells and weakened the binding of E2F1 to the NPRL2 promoter. Functionally, FOXO1 overexpression significantly slowed the proliferation of PC3 and LNCaP cells and also decreased E2F1 enhanced cell proliferation. In summary, this study revealed a novel FOXO1/E2F1‐NPRL2 regulatory axis in prostate cancer. E2F1 binds to the NPRL2 promoter and activates its transcription, while FOXO1 interacts with E2F1 and weakens its transcriptional activating effects. These findings help expand our understanding of the prostate cancer etiology and suggest that the FOXO1/E2F1‐NPRL2 signaling axis might be a potential target.